(untitled) (El Hilo de la Fabula, 2025)
The text by Cortázar that best captures his affection for animals is the prologue ‘A Stroll Among the Cages’, written as a letter to the Italian publisher Franco Maria Ricci. In it, Cortázar reflects on I segni dell’uomo, Ricci’s luxury collection featuring engravings from the Bestiary by Austrian dyer Aloys Zötl—fantastical animals, drawn motionless inside glass boxes. The letter, later included in Cortázar’s Territorios (1978, a miscellany of prologues), through its commentary on Zötl’s book, actually narrates a brief autobiography of the Argentinian writer. He refers to the ‘humanimals’ of his childhood: small, large, ambiguous, and dark beings which are a distorted and mirrored expression of young Cortázar’s childlike love for the animal kingdom; beings that, as he himself confessed, were completely unable to communicate with him and filled his life with unsuspected terrors. The letter contains two additional levels of interpretation: 1) a reflection on literary creation and Cortázar’s approach to writing literature, because through animal descriptions, the writer reveals the various literary forms that compose his texts (autobiography, short tales, reflections, irony, and linguistic games); 2) a confession of his multiple obsessions with language and with events in his life experienced as nightmares (like the axolotls in Paris, the crowing of roosters when he was three years old, the fear of beetles and ants, etc.). By using animal metaphors, Cortázar reveals his passion for analogy, which allows him, in a unique way, to speak of those ‘cracks’ in everyday life that lead him to Otherness—that invisible dimension, that ‘timeless land’ through which he is able to glimpse the infinite.